Alzheimer's Disease and Type 2 Diabetes: A Critical Assessment of the Shared Pathological Traits - Chatterjee, Shreyasi; Mudher, Amritpal (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) and Type 2 Diabetes Mellitus (T2DM) are two of the most prevalent diseases in the elderly population worldwide. A growing body of epidemiological studies suggest that people with T2DM are at a higher risk of developing AD. Likewise, AD brains are less capable of glucose uptake from the surroundings resembling a condition of brain insulin resistance. Pathologically AD is characterized by extracellular plaques of A and intracellular neurofibrillary tangles of hyperphosphorylated tau. T2DM, on the other hand is a metabolic disorder characterized by hyperglycemia and insulin resistance. In this review we have discussed how Insulin resistance in T2DM directly exacerbates A and tau pathologies and elucidated the pathophysiological traits of synaptic dysfunction, inflammation and autophagic impairments that are common to both diseases and indirectly impact A and tau functions in the neurons. Elucidation of the underlying pathways that connect these two diseases will be immensely valuable for designing novel drug targets for Alzheimer’s disease.